2020
DOI: 10.5603/fm.a2019.0134
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of the abductor pollicis longus: a pilot study

Abstract: Background:The abductor pollicis longus (APL) originates from the lateral part of the dorsal surface of the body of the ulna below the insertion of the anconeus muscle, from the interosseous membrane, and from the middle third of the dorsal surface of the body of the radius. However, the number of its accessory bands and their insertion vary considerably.Material and methods: Fifty upper limbs (2 paired, 31 male, 19 female) were obtained from adult Caucasian cadavers, and fixed in 10 % formalin solution before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…The presence of additional structures can lead to compression syndromes, tendovaginitis with limb overload, osteoarthritis and others. De Quervain syndrome, first carpometacarpal arthritis and trapeziometacarpal subluxation are examples of complications that may develop as a result of the described variations in the APL muscle [7,10]. The knowledge of accessory muscle tendons can be used for the needs of plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of additional structures can lead to compression syndromes, tendovaginitis with limb overload, osteoarthritis and others. De Quervain syndrome, first carpometacarpal arthritis and trapeziometacarpal subluxation are examples of complications that may develop as a result of the described variations in the APL muscle [7,10]. The knowledge of accessory muscle tendons can be used for the needs of plastic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical variations in this area and the APL respectively, are characteristic for a variety of pathology f.e De Quervain's Syndrome, first carpometacarpal arthritis, and trapeziometacarpal subluxation [7,10]. They might influence joint functionality, which underlines the significance of upper limb anomalies in the operative clinical setting and eventually alter therapeutic outcomes [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during the last seventy years, several studies (Lacey et al, 1951;Coleman et al, 1953;Baba, 1954;Jackson et al, 1986;Brunelli et al, 1991;Khoury et al, 1991;van Oudenaarde, 1991;Yuksel et al, 1992;Fabrizio et al, 1996;Dos Remédios et al, 2005;Shiraishi et al, 2005;Kulthanan et al, 2007;Paul et al, 2007;Mehta et al, 2009;Bravo et al, 2010;Roy et al, 2012;El-Beshbishy et al, 2013;Thwin et al, 2014;Tewari et al, 2015;Lee et al, 2017;Palatty et al, 2018;Xu et al, 2018;Karauda et al, 2020;Deivasigamani et al, 2021;Gnanasekaran et al, 2021) have shown that the APL tendon is much more variable than reports from the classical literature suggests, reaching proportions of 74.41 % and 85 % according to Roy et al (2012) and Bravo et al (2010) respectively. The anatomical diversity ranges from supernumerary tendons to variations of the point of insertion or tendons that divide themselves into various tendinous slips.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical structures tend to vary and can surprise us with their morphological variations [12,26,27]. Such fluctuations are quite common among ligaments, muscles, and their tendons [1,6,7,11,[21][22][23][24][25]. Although scientists know a lot about the morphology of the FCL, it can still present some new features.…”
Section: Introductionmentioning
confidence: 99%